2022
DOI: 10.1155/2022/6543953
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application of Tactics in Technical and Tactical Analysis of Table Tennis Mixed Doubles Based on Artificial Intelligence Graph Theory Model

Abstract: Objective. To construct the graph theory model and grey correlation model of table tennis mixed doubles technology and tactics so as to provide a new research method for the analysis of table tennis mixed doubles technology and tactics. The method of graphic theory and video observation is used to study the top tactical indicators of the game, and the method of graphic theory and video observation is used to analyze the tactical data of men and women, which has a certain contribution to the world level of tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…is study introduces the application of multiple regression analysis in table tennis mixed doubles. In subsequent studies, deep analysis and discussion of singles or doubles [20][21][22][23][24]. Besides, in practice, in commercial, construction, or other sports games, it can solve many practical problems.…”
Section: Study Conclusionmentioning
confidence: 99%
“…is study introduces the application of multiple regression analysis in table tennis mixed doubles. In subsequent studies, deep analysis and discussion of singles or doubles [20][21][22][23][24]. Besides, in practice, in commercial, construction, or other sports games, it can solve many practical problems.…”
Section: Study Conclusionmentioning
confidence: 99%
“…In order to find the best algorithm for prediction accuracy, this study compares the performance of LSTM-BPNN with six classical artificial intelligence algorithms, which are BPNN, XGB, RF, ET, DT and KNN, in terms of the mean squared error (MSE), mean absolute error (MAE), root mean square error (RMSE), and coefficient of determination ( R 2 ), as shown in Eqs. (23)(24)(25)(26). Table 4 shows the testing results of LSTM-BPNN, BPNN, DTR, XGBR, RFR, KNN and ETR.…”
Section: Resultsmentioning
confidence: 99%
“…The most usual method or theory is the traditional three-phase evaluation theory 1 . Based on that, phase-based theories have been proposed to improve it, such as the four-phase evaluation theory 3 and the double three-phase evaluation theory 7 in the descriptive analysis range 14 .With the rapid development of deep learning and machine learning, many models and algorithms have been applied to study table tennis matches [15][16][17][18][19][20][21][22][23][24][25] . Researchers have built models and adjusted input values through simulations to achieve technical-tactical diagnosis 15,16,18,19,21 based on sports training and competition methods or theories.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%